Absorção e distribuição de nitrogênio, fósforo e potássio em sorgo granífero (Sorghum bicolor (L.) Moench), em função da adubação nitrogenada - Silveira Carvalho, Orozimbo; Nogueira Fontes, Luiz Antônio; Moura Filho, Waldemar; Cardoso, Antônio Américo; Defelipo, Braz Vitor (Revista Ceres, 2025)
Studies were made to evaluate the influence of nitrogen fertilizer on the absorption and distribution of N, P and K within the aerial parts of grain sorghum Pplants. The reason for these studies was to obtain data which would contribute to a better understanding of the nutritional requirements of grain sorghum, from its initial stages of growth to its physiological maturity.